The Human Respiratory Microbiome: Implications and Impact - Mitchell, Alicia B.; Glanville, Allan R. (Seminars in Respiratory and Critical Care Medicine, 2018)
Once considered a sterile site below the larynx, the tracheobronchial tree and parenchyma of the lungs are now known to harbor a rich diversity of microbial species including bacteria, viruses, fungi, and archaea. Many of these organisms, particularly the viruses which comprise the human respiratory virome, have not been identified, so their true role is unknown. It seems logical to conclude that a “healthy” respiratory microbiome exists which may be modified in disease states and perhaps by therapies such as antibiotics, antifungals, and antiviral treatments. It is likely that there is a critical relationship or equilibrium between components of the microbiome until such time as perturbations occur which lead to a state of dysbiosis or an “unhealthy” microbiome. The act of lung transplantation provides an extreme change to an individual's respiratory microbiome as, in effect, the donor respiratory microbiome is transplanted into the recipient. The mandatory ex-vivo period of the donor lungs appears to be associated with blooms of resident viral species in particular. Subsequently, allograft injury, rejection, and immune suppressive therapy all combine to create periods of dysbiosis which when combined with transient infections such as community acquired respiratory viruses may facilitate the development of chronic allograft dysfunction in predisposed individuals. As our understanding of the respiratory microbiome is rapidly expanding, based on the use of new-generation sequencing tools in particular, it is to be hoped that insights gained into the subtle relationship between the microbiome and the lung allograft will facilitate improved outcomes by directing novel therapeutic endeavors.
Keywords: microbiome; lung transplant; lung allograft; respiratory tract; virome